Urgensi asesmen dalam bimbingan dan konseling dalam menyiapkan generasi berkualitas - Fitriana Fitriana; Yulianti Yulianti; A. Muri Yusuf; Daharnis Daharnis (SCHOULID: Indonesian Journal of School Counseling, 2021)
Students can develop in an optimal direction, which is the dream of each individual, parents, teachers, and the whole community, especially with the condition of a quality generation. The quality of the generation is not achieved quickly, but rather the process and cooperation between personnel, one of which is Guidance and Counseling teachers. Guidance and Counseling teachers act as one of the core personnel in developing students' potential. The implementation is of course adapted to the needs of students because each individual is unique, so the urgency of assessment in guidance and counseling is unavoidable. Through the assessment, a lot of information was obtained, the majority of which were authentic and systematic, so that Guidance and Counseling teachers could easily follow up on the results of the assessment. Furthermore, to deepen this matter, a research is carried out using the method data collection in the form of decommunation. This article aims to elaborate the theory in the form of 1) understanding of guidance and counseling assessment 2) principles of guidance and counseling assessment, 3) the urgency of guidance and counseling assessment in preparing a quality generation.